“The lying’st knave in Christendom”: The Development of Disability in the False Miracle of St. Alban’s - Row-Heyveld, Lindsey (Disability Studies Quarterly, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Cambria; mso-fareast-font-family:Cambria; mso-hansi-font-family:Cambria;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> This article examines various retellings of a single story to explore how conceptions of disability changed throughout the English Reformation. The tale of a false miracle feigned and revealed in the village of St. Alban’s during the reign of Henry VI was recounted by a number of authors: Thomas More, Richard Grafton, John Foxe, and, finally, William Shakespeare. More’s version imagines a disability that is shaped by an understanding of mutual exchange between disabled and able-bodied persons. The Reformation eliminated that exchange, and its loss is reflected in the other accounts of the false miracle of St. Alban’s where disability is imagined as increasingly dangerous, deceptive, and emasculating. I argue that Shakespeare, in particular, expands negative post-Reformation ideas about disability in 2 Henry VI, while simultaneously demonstrating the inability to contain disability in a period that anxiously struggled to define and regulate it.